Pre-Greek : phonology, morphology, lexicon - Beekes, R. S. P. (Robert Stephen Paul) (Brill introductions to Indo-European languages, 2014)
Robert Beekes collects and analyzes the evidence for Pre-Greek, the non-Indo-European language which disappeared prehistorically due to a language shift to Greek, but left many traces in the Greek lexicon.